Halal-based healthcare service: patients’ experiences and challenges in performing solah in hospital - Abdul Halim, Ratna Zuhairah; Saidi, Sanisah; Mohamad Ismail, Mohamad Firdaus; Mohd Yusof, Nazri; Che Ahmad, Aminudin (Lokman Hekim University, 2024)
Solah, a fundamental Islamic practice, faces notable challenges in hospitals, with many patients not performing it. The reason for this situation is unclear. This study aims to uncover patients' experiences and challenges with solah during hospitalisation. Methods: Employing a qualitative single-embeded case study design approach, adults who are Muslim, have been in the tertiary teaching hospital for over 24 hours, and understand Malay or English were selected. Data collection using multiple methods involved in-depth interviews, observations, and document analysis, analyzed through framework analysis and triangulation to gain comprehensive insights. Findings: Between October 2021 and August 2022, eighteen participants highlighted issues such as physical limitations, lack of facilities, insufficient guidance from healthcare professionals (HCPs), and misconceptions about solah obligations, including the concept of rukhsoh, taharah (cleanliness) and darurah. Enhancing patient care involves improving communication, understanding patient needs, and providing support and information about solah. Conclusion: attitudes, knowledge, and misconceptions about religious practices affect patients' ability to engage in solah, underscoring the need for effective communication and patient-centered approaches in healthcare settings.